2006
DOI: 10.1016/j.ccr.2006.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Selective killing of oncogenically transformed cells through a ROS-mediated mechanism by β-phenylethyl isothiocyanate

Abstract: Reactive oxygen species (ROS) stimulate cell proliferation and induce genetic instability, and their increase in cancer cells is often viewed as an adverse event. Here, we show that such abnormal increases in ROS can be exploited to selectively kill cancer cells using beta-phenylethyl isothiocyanate (PEITC). Oncogenic transformation of ovarian epithelial cells with H-Ras(V12) or expression of Bcr-Abl in hematopoietic cells causes elevated ROS generation and renders the malignant cells highly sensitive to PEITC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
899
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,019 publications
(940 citation statements)
references
References 42 publications
36
899
1
4
Order By: Relevance
“…We found that NAMPT knockdown sensitized PC3 cells to these chemotherapeutic agents with the most dramatic effect on PEITC (Figure 5d and Supplementary Nicotinamide phosphoribosyltransferase and prostate cancer B Wang et al Figure 5). PEITC induces cancer cell apoptosis by disabling glutathione antioxidant system, causing severe accumulation of cellular reactive oxygen species and oxidative mitochondrial damage (Trachootham et al, 2006;Xiao et al, 2006). The significant effect of NAMPT knockdown on PEITC killing of prostate cancer cells resembles the effect of H 2 O 2 treatment described above.…”
Section: Nampt Is Overexpressed In Human Prostate Cancermentioning
confidence: 73%
“…We found that NAMPT knockdown sensitized PC3 cells to these chemotherapeutic agents with the most dramatic effect on PEITC (Figure 5d and Supplementary Nicotinamide phosphoribosyltransferase and prostate cancer B Wang et al Figure 5). PEITC induces cancer cell apoptosis by disabling glutathione antioxidant system, causing severe accumulation of cellular reactive oxygen species and oxidative mitochondrial damage (Trachootham et al, 2006;Xiao et al, 2006). The significant effect of NAMPT knockdown on PEITC killing of prostate cancer cells resembles the effect of H 2 O 2 treatment described above.…”
Section: Nampt Is Overexpressed In Human Prostate Cancermentioning
confidence: 73%
“…RAS-transformed tumor cells upregulate ROS levels and are more susceptible to oxidative stress relative to their untransformed counterparts (Trachootham et al, 2006;Yagoda et al, 2007), likely through imbalances in their antioxidant pathways (Trachootham et al, 2009) (Supplementary Figure S1). In BJ cells, oncogenic RAS expression upregulates MTH1 levels ( Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…In this study we have shown that androgen can increase the basal ROS levels through NOX2 and NOX4, an effect that is blocked by apocynin or androgen receptor blockade. Unlike severe or excessive accumulation of ROS that triggers a pro-apoptotic toxic event in cancer cells, 25,26 reducing the basal ROS levels by means of apocynin or ADT reset the adaptive molecular machinery of the cells rendering it much more vulnerable to toxic oxidative stress as induced by radiation therapy (8 and Figure 6) The potential future clinical application of apocynin as a radiation sensitizer is appealing. It is a natural organic compound that acts as a NOX inhibitor by preventing the assembly of its subunits.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Accordingly, it has been shown to be effective in preventing the production of the superoxide in human white blood cells. 29 It does not, however, obstruct the phagocytic or other defense roles of granulocytes including intracellular killing, 26 and so may be widely used as an inhibitor of NOX. 30,31 Obviously, preclinical in-vivo studies are needed before the use of apocynin as an alternative to ADT for radiation sensitization in PC can be explored in clinical trails, but our findings establish a proofof-principle for this concept.…”
Section: Discussionmentioning
confidence: 99%